Analisis pendapatan pedagang makanan dan minuman di area wisata Gentala Arasy Kelurahan Arab Melayu Kecamatan Pelayangan Kota Jambi - Muhammad Safri; Jaya Kusuma Edy; Ichsan Al Farisy (Jurnal Dinamika Manajemen, 2023)
This study aims to determine the social and economic characteristics and analyze the factors that affect the income of food and beverage traders. This type of research is survey research with a quantitative descriptive approach. The data used is primary data and the sample used is 64 respondents with a data collection technique in the form of a questionnaire. The analysis technique uses multiple linear regression analysis. The results of the study found that social characteristics were seen from group age, gender and education level while economic characteristics were seen from, working capital, working hours, number of goods sold, length of business and income. The results of data processing show that the variables of working capital, working hours, the number of goods sold and the length of business together have a significant effect on the income of traders and partially the variables that have a significant and positive effect on income are the variables of working capital, working hours and the number of goods sold . While the length of business variable has no significant effect on income.